Base‐Free Non‐Noble‐Metal‐Catalyzed Hydrogen Generation from Formic Acid: Scope and Mechanistic Insights. Issue 42 (4th September 2014) - Mellmann, Dörthe; Barsch, Enrico; Bauer, Matthias; Grabow, Kathleen; Boddien, Albert; Kammer, Anja; Sponholz, Peter; Bentrup, Ursula; Jackstell, Ralf; Junge, Henrik; Laurenczy, Gábor; Ludwig, Ralf; et al.
Abstract: The iron‐catalyzed dehydrogenation of formic acid has been studied both experimentally and mechanistically. The most active catalysts were generated in situ from cationic Fe II /Fe III precursors and tris[2‐(diphenylphosphino)ethyl]phosphine (1, PP3 ). In contrast to most known noble‐metal catalysts used for this transformation, no additional base was necessary. The activity of the iron catalyst depended highly on the solvent used, the presence of halide ions, the water content, and the ligand‐to‐metal ratio. The optimal catalytic performance was achieved by using [FeH(PP3 )]BF4 /PP3 in propylene carbonate in the presence of traces of water. With the exception of fluoride, the presence of halide ions in solution inhibited the catalytic activity. IR, Raman, UV/Vis, and EXAFS/XANES analyses gave detailed insights into the mechanism of hydrogen generation from formic acid at low temperature, supported by DFT calculations. In situ transmission FTIR measurements revealed the formation of an active iron formate species by the band observed at 1543 cm −1, which could be correlated with the evolution of gas. This active species was deactivated in the presence of chloride ions due to the formation of a chloro species (UV/Vis, Raman, IR, and XAS). In addition, XAS measurements demonstrated the importance of the solvent for the coordination of the PP3 ligand. Abstract : Fe‐catalyzed H2 generation : The iron‐catalyzed dehydrogenation of formic acid has been studied both experimentally and mechanistically. Optimization of the reaction conditions led to a highly efficient catalyst system that is comparable in activity to most known noble‐metal catalysts used for this transformation (see figure). The key to an active catalyst is the appropriate choice of ligand.